Condition Factors and Growth Patterns of Mantis Shrimp (Harpiosquilla raphidea) in the Estuary Waters of Berombang River, Labuhanbatu Regency, North Sumatera - Yulistiani Yulistiani; Rivo Hasper Dimenta (BIOEDUSCIENCE, 2022)
Background: Mantis shrimp is one of the favorite shrimp caught by fishermen around the estuary waters of Berombang River, Labuhanbatu Regency. This study aimed to determine the condition factors and growth patterns of mantis shrimp population. Method: Three station points were determined using a purposive random sampling method. The sampling of Harpiosquilla raphidea was carried out using trawl nets. The data analysis provided information on growth patterns and condition factors. Result: The results showed that the growth patterns of male H. raphidea belonged to the positive b> 3 allometric category, where weight growth was faster than carapace growth. Moreover, the growth patterns of female H. raphidea belonged to the negative b<3 allometric category, where the carapace growth was faster than body weight growth. The value of Fulton (K) condition factors for male H. raphidea ranged from 3.54 to 13.18, and for females, it ranged from 15.28 to 22.09. The value of correlation analysis of Physic-chemical parameters, water temperature (0.935) and DO (0.832) showed the high category correlation test results. Conclusion: This result showed that from November 2021 to January 2022, the condition of H. raphidea population around the estuary waters of Berombang River was known and predicted to be in the adult stage